2021
DOI: 10.1007/s42250-020-00213-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Chemistry of Bioactive Compounds from Plants and Soil Microbes: a Review

Abstract: Bioactive compounds derived from plants and microbial sources are required for the survival of the human race and groundbreaking research must continue in this line. Plants and microbes are the major sources of naturally occurring bioactive compounds for numerous biotechnological applications. Recent progress in the fields of bioactive compounds and soil chemistry in agriculture has since given man a lead to the discovery of potent drugs that combat both human and plant diseases. The soil provides the medium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 139 publications
(118 reference statements)
0
22
0
1
Order By: Relevance
“…Experiences of the COVID-19 show that poor people living in neighborhoods polluted with the wastewaters flowing in the streets are more infected or dead than affluent people in clean places [28][29][30]. Therefore, well-treated sewage can protect health against this disease [31].…”
Section: Theoretical Explorationmentioning
confidence: 99%
“…Experiences of the COVID-19 show that poor people living in neighborhoods polluted with the wastewaters flowing in the streets are more infected or dead than affluent people in clean places [28][29][30]. Therefore, well-treated sewage can protect health against this disease [31].…”
Section: Theoretical Explorationmentioning
confidence: 99%
“…The extraordinary advantages of bioactive molecules as a source of biotherapeutics are beyond question [9,10]. Studies have identified more than 5000 individual phytochemicals, and this number is continuously increasing due to the introduction of new and efficient isolation and characterization techniques [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies showed that many herbs are rich in phenols, flavonoids, tannins, vitamins, and many more phytochemicals [9,10,15,16]. Moreover, researchers in the last few years have shown an increasing interest in these compounds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemicals from different medicinal plants were playing very crucial role in development of new drugs with broad spectrum usage including liver diseases [14,15]. Many bioactive compounds were reported from medicinal plants and about their protective nature against liver diseases [16][17][18][19]. But still many plants are available to know about their medicinal value.…”
Section: Introductionmentioning
confidence: 99%